Audit Teknologi Informasi (TI) Penguatan Proses Audit Teknologi Informasi Melalui Integrasi Framework Togaf - Dinata, Aria; Sutabri, Tata (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
Information Technology (IT) audit is a critical process that ensures the IT infrastructure within an organization operates effectively and aligns with its strategic objectives. However, with the increasing complexity of IT architecture, a more structured and holistic approach is required. This study aims to analyze how the TOGAF framework can be integrated into the IT audit process to enhance its effectiveness. Through a literature review involving 15 scientific references, it was found that TOGAF integration can improve the alignment between IT architecture and business strategy, enhance risk management, and ensure compliance with relevant regulations. TOGAF also provides a structured guideline for auditors to comprehensively assess IT architecture. The findings of this study suggest that the TOGAF framework offers an effective solution to address the growing challenges in IT audits by providing a comprehensive and measurable approach. Keywords— Information Technology Audit, TOGAF, IT risk management, regulatory compliance, IT architecture, business strategy